Effects of synthetic cathinone naphyrone in the conditioned place preference test - Evidence of its addictive potential - Danda, Hynek; Pinterová-Leca, Nikola; Šíchová, Klára; Štefková-Mazochová, Kristýna; Syrová, Kateřina; Olejníková, Lucie; Končická, Markéta; Mazoch, Vladimír; Lhotková, Eva; Kuchař, Martin; Páleníček, Tomáš (Behavioural brain research, 2022)
Naphyrone, also known as NRG-1, is a novel psychoactive substance (NPS), a cathinone with stimulatory properties available on the grey/illicit drug market for almost a decade. It is structurally related to infamously known powerful stimulants with the pyrovalerone structure, such as alpha-pyrrolidinovalerophenone (α-PVP) or methylenedioxypyrovalerone (MDPV) that are labeled as a cheap replacement for cocaine and other stimulants. Despite the known addictive potential of α-PVP and MDPV, there are no studies directly evaluating naphyrone's addictive potential e.g., in conditioned place preference (CPP) test or using self-administration. Therefore, our study was designed to evaluate the addictive potential in a CPP test in male Wistar rats and compare its effect to another powerful stimulant with a high addictive potential - methamphetamine. Naphyrone increased time spent in the drug-paired compartment with 5 and 20 mg/kg s.c. being significant and 10 mg/kg s.c. reaching the threshold (p = 0.07); the effect was comparable to that of methamphetamine 1.5 mg/kg s.c. The lowest dose, naphyrone 1 mg/kg s.c., had no effect on CPP. Interestingly, no dose response effect was detected. Based on these data, we are able to conclude that naphyrone has an addictive potential and may possess a significant risk to users.
Keywords: methamfetamin; Animals; Rats; vztah mezi dávkou a účinkem léčiva; Methamphetamine; Rats, Wistar; pyrrolidiny; alkaloidy; chování zvířat; Pyrrolidines; Conditioning, Classical; Dose-Response Relationship, Drug; Male; Alkaloids; klasické podmiňování; modely nemocí na zvířatech; pentanony; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; Substance-Related Disorders; stimulanty centrálního nervového systému; zvířata; mužské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Central Nervous System Stimulants; Pentanones; potkani Wistar